Integrative-project Model of Environmental Education in the Training System of the Students - Nelyubina, Elena G.; Safina, Lily G.; Bobkova, Elena Yu.; Korobejnikova, Elena V.; Melysheva, Ekaterina P. (International Journal of Economics and Financial Issues, 2016)
education and population enlightenment become the first priority. The principles and objectives of environmental education should be formulated in accordance with the social order, which is given to the education system from the whole society: the formation of a harmoniously developed personality as an ideal and a supreme value. In this case, the education of a rational attitude to nature is seen as a component of personal diversification. In this regard, an urgent analysis is required by the questions of selection of scientific material in the content of academic disciplines, methods and technical means of its transmission. The integrated education is the foundation, the heart of understanding the problems of development of both the person and the environment. We have worked out an integrative-project model of environmental education of university students, which is based on didactic principles of environmental education: scientific, systematic, continual and consequential, integrative, linking theory to practice, problematic, the principles of professional orientation, activity, regionalization, humanization and humanitarization. Keywords: higher education, professional competency, integrative, environmental education JEL Classifications: I2, I24, P36